MESHING THEORY ANALYSIS OF THE MODIFIED ROLLER ENVELOPING HOURGLASS WORM DRIVE - QI Yan; LIAO HongHui; WANG XuDong; LIU ZaiXin; LI JinKuan (Jixie qiangdu)
Based on the modification of the single-roller-enveloped toroidal meshing worm drive, a parabolic modified roller-enveloped toroidal meshing worm drive is obtained. According to the spatial meshing theory and the transmission characteristics of the parabolic modified roller-enveloped toroidal meshing worm drive, the basic mathematical model is established; based on the mathematical model of parabolic modified roller enveloping toroidal meshing worm transmission, the basic characteristic parameters of the new worm transmission are deduced, and the meshing performance of the new worm transmission is further analyzed. The basic performance is very good.